CHILD PROTECTION IN THE CRIMINAL JUSTICE SYSTEM TOWARDS RESTORATIVE JUSTICE IN THE MIDDLE OF THE COVID-19 PANDEMIC - Kharismunandar, Jhuanda Fratama; Appludnopsanji, Appludnopsanji; Kurniawan, Syukri (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
Children are an almighty gift and are a treasure and the next generation of the nation for the better progress of the country in the future. The existence of a child's status has become the main conversation and is protected by law. Many cases of child abuse and dealing with the law as victims and perpetrators traumatize children and damage their future. So that it needs to be done efforts to protect children to protect the rights and interests and needs of children. The rise of COVID-19that spreads in the environment has many negative impacts, not only is it dangerous for humans but the presence of COVID-19influences performance so that the law enforcement audience is hampered. In this case, it would be appropriate if the settlement of the child case during the COVID-19pandemic was to use diversion efforts that did not relinquish the goal of achieving restorative justice. The research method of this article uses doctrinal and is assisted with a conceptual, analytical, legislative, and case approach and supplemented with primary, secondary, and tertiary legal materials to complete the data needs of this study. Settling child cases amid a COVID pandemic 19 makes it very impossible to use the juvenile justice system using litigation, considering that not only parents who are prone to age but children are also prone to health infected with COVID 19. So the implementation of the juvenile criminal justice system using litigation can endanger the psychic children and their parents.Â